The appraisal of new concession agreement between Pharmaniaga Logistic Sendirian Berhad (PLSB) and Hospital Seberang Jaya (HSJ) - Soh Tek Sui @ Hussin, Mohamad Hafizzi; Mohamad, Mohammad Irfan Fahmie (2012)
To ensure the supply of medicines and medical products by Pharmaniaga Logistic Sdn. Bhd. (PLSB) through approved purchased product list (APPL) can be done effectively and efficiently, both Ministry of Health Malaysia and Pharmaniaga Logistics Sdn. Bhd. agreed to sign up one concession agreement in 1994. 15 years later, both sides have agreed to sign up a new concession agreement, which has been improved and become fairer to both sides. Generally, this study was carried out to assess to what degree the New Concession Agreement been obeyed by PLSB using Hospital Seberang Jaya as the base of investigation. This retrospective cross sectional study is done in the aid of data collection form. Using ten key performance standard that has been highlighted in New Concession Agreement, we take a look at all previous business transaction records starting 16th March 2011 until 30lh June 2011 involving approved purchased product list (APPL) items. The major finding in this research is we all know that key performance standards that most being neglected by Pharmaniaga Logistic Sdn. Bhd. was “delivery of products more than seven days from the date of local purchased order form sent”. Almost 8.9% of business transactions involving APPL products were found problematic. Surprisingly, others key performance standard were fine. The incident of others key performance standards being neglected was low and even for some key performance standard such as “delivery of product in emergency case in the period of 24 hours from local purchased order was sent” is none at all. Others finding that we get from this research is there will be penalty for each incident of neglected key performance standard. The type of penalty is different according to types of key performance standard that has been neglected or disobey by Pharmaniaga Logistic Sdn. Bhd. In a nutshell, this New Concession Agreement between Pharmaniaga and Ministry of Health Malaysia just need some adjustment and re-evaluation, to ensure the supply of both medical and non medical item can be done effectively and efficiently without any problems.